Finance and Development, September 1970. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1970)
This paper analyzes the impact of economic development on the environment. The paper highlights that the environmental impact of the industrial process includes everything from the effects of withdrawing the inputs for industry from nature, through the effects of transforming the inputs into salable products, the effects of using the products, and the effects of disposing of what remains after the product no longer has an economic use. The heart of the problem is that almost none of these impacts of industrial processes can readily be costed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet